Photocatalytic degradation of crude oil pollutants in water resources via magnetic nanocomposite - Salihi, Nawar Razzaq; Kol, Zeliha Betul; Duranoglu, Dilek (ELSEVIER, 2026)
Crude oil leakage into water resources can alter taste, odor, color, and chemical properties, introducing harmful organic compounds that are difficult to remove. This study aimed to apply an effective technique for achieving high removal efficiency of these pollutants using a magnetic NiOCoO/SiO2/TiO2 photocatalyst, developed through a combination of co-precipitation and sol-gel methods. The prepared catalysts were characterized using XRD, which confirmed the presence of NiO, CoO, and TiO2 phases. FESEM-EDS analysis revealed a heterogeneous morphology with crystalline NiOCoO and amorphous SiO2 structures. The spherical form of TiO2 particles indicated uniformly distributed multiphase structure. Particle size analysis indicated an average size of similar to 305 nm, while vibrating sample magnetometer (VSM) measurements demonstrated superparamagnetic behavior of NiOCoO/SiO2/TiO2 catalyst with a saturation magnetization of 1.42 emu/g. Using the UV/Vis diffuse reflectance spectra (DRS), the absorption of the UV and visible light of the photocatalyst was done to characterize NiO-CoO/SiO2/TiO2 composite and band gap value was found about 1.56 eV. A photoreactor equipped with 90 W ultraviolet light (365 nm) was employed to assess the photocatalytic efficiency of the synthesized composite for the degradation of crude oil pollutants in water. NiOCoO/SiO2/TiO2 magnetic photocatalyst demonstrated excellent performance, with the removal efficiencies of 97.7 % for crude oil, 97.4 % for chemical oxygen demand (COD), and 94.5 % for total organic carbon (TOC). The NiOCoO/SiO2/TiO2 composite showed faster kinetics than the commercial TiO2 photocatalyst, with a half-life of 45.45 min vs. 95.08 min and a rate constant of 0.015 min(-1) vs. 0.0073 min(-1). Moreover, the photocatalyst was magnetically recovered and successfully reused throughout 10 cycles.
Keywords: Crude oil pollutant; Photocatalytic degradation; Magnetic photocatalyst; Cobalt oxide; Nickel oxide; Titanium dioxide; PERFORMANCE; COMPOSITE; Chemistry; Materials Science; Physics